EU Measures ‘against’ Turkey through the Lens of International Law Dynamics (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The threats of climate change in the Eastern Mediterranean area should encourage cooperation among the coastal States and with the EU. Unauthorized drilling activities in 2018 have further affected already troubled European neighbourly relations with the Republic of Turkey and led the EU to impose targeted restrictive measures. The article focuses on targeted decisions and regulations adopted by the EU. The analysis develops against the backdrop, on the one hand, of the unsolved Cyprus issue and, on the other, of environmental risks in the Eastern Mediterranean.
Keywords: Turkey; EU Restrictive Measures; Association Process; Eastern Mediterranean; Maritime Boundary Delimitation; Cyprus; International Law; Sovereignty; UN Mission of Good Offices; Environmental Threats